Pioneer Manuscript in Refuting Wahhabism: The Perspective of Kiai Dimyati bin Abdul Karim as-Surakarta as a Basis for Islamic Moderation - Muhyidin Muhyidin; Triyono Triyono; Mira Novana Ardani (Diponegoro University, 2022)
The study of manuscripts on religious moderation, especially those related to counter extremist and Wahhabi doctrines, missed a manuscript written in 1926. The manuscript was written by Kiai Muhammad Dimyati bin Abdul Karim as-Surakarta, under the title Lawāmi'ul Burhān wa Qawāṭi'ul Bayān. The main motivation in writing the manuscript was to educate people so that they are not influenced by wahhabism. This research is a study of manuscript Lawāmi'ul Burhān wa Qawāṭi'ul Bayān by Kiai Muhammad Dimyati. The manuscript has perspective about the importance of rising together against the narrow Islam of Wahhabism; Islam suppresses local cultural expressions, feels right about himself, seems unfriendly and different, and also downplays the role of women. This article finds that Kiai Muhammad Dimyati bin Abdul Karim has conducted a critical study of the Wahhabi doctrine, which according to him is mono-perspective and does not tolerate differences in interpreting Islamic law (mazhab).